Marginalization of pedagogy - Nalaskowski, Aleksander (Przegląd Badań Edukacyjnych (Educational Studies Review), 2013)
The article deals with the situation of Polish pedagogy as an academic science. The author shows the processes leading to marginalization, or even disregard of pedagogy in the currant structure of management of science. The article presents legal and customs-related paradoxes due to which pedagogy loses its identity and grows in the shadow of other social studies.